A Questionnaire Based Survey with Physicians for Effectiveness and Tolerability of Secnidazole in Periodontitis at Sri Lanka. Issue 5 (2022) - Senanayake, Asanka; Pawar, Dilip; Shinde, Amol
No abstract available